Review of high entropy ceramics: design, synthesis, structure and properties - Zhang, Rui-Zhi; Reece, Michael J (Journal of materials chemistry. A, Materials for energy and sustainability, 2019)
High entropy ceramics are novel materials with no less than four different cations or anions. The development of high entropy ceramics follows the 'configurational entropy stabilized single phase' concept, which was first demonstrated for high entropy metal alloys in 2004. The advantages of high entropy ceramics are their compositional and structural diversity, and many of them have a band gap, which makes them potential functional materials for a wide range of applications. They have recently generated significant interest with the publication of 70+ related papers since 2015. In this review we have summarized the recent progress in this rapidly growing field. We emphasize the progress by researchers to answer the following three fundamental questions for high entropy ceramics: (1) which combinations of cations or anions can be synthesized as single-phase materials; (2) are the component elements truly random down to the atomic scale; and (3) what new physics, properties and applications will the incorporation of multi-elements elements bring. These fundamental questions are still open at this stage and warrant further studies. The objective of this review is to give a comprehensive overview of the literature to date on high entropy ceramics and to guide further investigation in this emerging field. Design models, synthesis methods, atomic scale structure characterization, properties and applications of high entropy ceramics are reviewed.